A new species of fan-throated lizard of the genus Sitana Cuvier, 1829 from coastal Kerala, southern India - Sadasivan, Kalesh; Ramesh, M. B.; Palot, Muhamed Jafer; Ambekar, Mayuresh; Mirza, Zeeshan A. (Zootaxa, 2018)
We here describe Sitana attenboroughii sp. nov., a new species of fan-throated lizard of the genus Sitana Cuvier, 1829 from coastal Kerala in southern India. The new species morphologically is closer to Sitana visiri Deepak, 2016 (in Deepak et al. 2016a), however, differs in having higher numbers of ventral scales and a comparatively short but richly colored dewlap. Genetically the new species shows affinity to Sitana marudhamneydhal Deepak, Khandekar, Varma & Chaitanya, 2016 from which it differs in an uncorrected pairwise sequence divergence of 2.2% for a fragment of mitochondrial Nicotinamide adenine dinucleotide dehydrogenase (NADH) subunit 2 gene.